Kinematics model and trajectory interpolation algorithm for CNC turning of non-circular profiles - Yang, Jixiang; Ai, Wu; Liu, Yaxiong; Chen, Bing (Precision engineering, 2018)
Non-circular profiles commonly appear in cams, camshafts and convex ellipse pistons that are widely used in the automobile and navigation areas. However, direct application of traditional CNC turning processes on non-circular profiles will cause periodically variable cutting angles and feedrates, which leads to fluctuating cutting forces and is detrimental to cutter life and surface quality. In order to guarantee constant cutting angles and uniform feedrates for CNC turning of non-circular profiles, kinematics model and trajectory interpolation algorithm are developed for an in-house developed non-circular turning prototype. First, the kinematics model for the specially designed non-circular turning prototype is developed in order to guarantee constant cutting angles during the non-circular turning process. Then the trajectory interpolation algorithm is developed to guarantee uniform feedrate by building the polynomial function between the arc-length and the profile parameter with error constraints. Finally, the proposed kinematics model and tool path interpolation algorithm are experimentally verified on the in-house developed non-circular turning prototype, and the results demonstrate that the proposed model and algorithm can guarantee steadier cutting angle and feedrates when compared with traditional turning processes with a constant speed of spindle rotation. Cutting tests show that the proposed technology can lead to lower cutting load disturbances, higher tracking and contour accuracy when compared with traditional turning processes. •A new tool holder mechanism is designed for the CNC turning of non-circular profiles.•The kinematics model is developed to guarantee constant cutting angle.•The trajectory interpolation algorithm is developed to guarantee uniform feedrate.•The proposed method obtains steadier cutting angle and feedrate than the traditional turning method.•The proposed method leads to lower cutting load variances, higher tracking and contour accuracy than the traditional method.